Salicylic acid relieves salt stress damage on basil growth - Iarley da Silva, Toshik; Salviano Lopes, Adriano; Gomes Dias, Marlon; Melo Gonçalves, Anderson Carlos; de Melo Filho, José Sebastião; Dias, Thiago Jardelino (Revista Ceres, 2023)
Salinity is one of the main challenges in agriculture, especially in arid and semi-arid regions. Salicylic acid application may be a strategy to mitigate the harmful effects of salt stress on plant growth. Basil (Ocimum basilicum) is a medicinal, spice, and ornamental plant grown around the world that has its growth reduced by salt stress. Therefore, the objective was to evaluate salicylic acid in mitigating the damage caused by salt stress in ‘Cinnamon’ basil. Growth was evaluated at 90 days after the start of irrigation with saline water. Salicylic acid application attenuates the harmful effects of salt stress on the number of leaves, number of inflorescences, leaf dry mass, inflorescence dry mass, root dry mass, seed mass, leaf area, leaf area ratio, specific leaf area, leaf mass ratio, root mass ratio, inflorescence mass ratio, Dickson quality index, sclerophilia index, robustness quotient and shoot root ratio. Salt stress decreased plant height, stem diameter, stem dry mass, and stem mass ratio of basil ‘Cinnamon’. Salicylic acid can be used to lessen the harmful effects of salt stress on basil ‘Cinnamon’.